Production Of Indole Acetic Acid By Three Anoxygenic Phototrophic Purple Bacteria - KADARI RAJYALAXMI,; SIVADEVUNI GIRISHAM, (International Journal of Pharma and Bio Sciences, 2015)
The present investigation Allochromatium sp. GSKRLMBKU-01, Rhodobacter sp. GSKRLMBKU-02 and Rhodobacter sp. GSKRLMBKU-03 were isolated from different ecological niches and its ability to produce Indole Acetic Acid (IAA) in the presence and absence of tryptophan as inducer was investigated. All the three bacteria produce IAA even in the absence and presence of tryptophan but production was more in tryptophan supplemented medium. The maximum IAA production by Allochromatium sp. GSKRLMBKU-01 (165 μg/ml), Rhodobacter sp. GSKRLMBKU-02 (140 μg/ml) and Rhodobacter sp. GSKRLMBKU-03 (120 μg/ml) was recorded. The highest amount of biomass and IAA production was recorded on 8th day of incubation by Allochromatium sp. GSKRLMBKU-01 and Rhodobacter sp. GSKRLMBKU-03, while Rhodobacter sp. GSKRLMBKU-02 was recorded on 10th day of incubation.